Preparation method of nano calcium carbonate with high dispersibility and high activation degree

By using polyepoxysuccinic dispersant and γ-glycidyl etheroxypropyl trimethoxysilane/XH-CS05/stearic acid composite surface treatment agent on nano calcium carbonate, the problem of difficulty in dispersing nano calcium carbonate in polymers is solved, and the preparation of nano calcium carbonate with high activation and high dispersion is achieved, and the material performance is improved.

CN119570289APending Publication Date: 2025-03-07HUBEI XINGFA CHEM GRP CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411593078.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

Nano calcium carbonate is difficult to disperse evenly in polymers, resulting in interface defects and degradation of material properties. Its high surface energy and strong polarity make it easy to form agglomeration, affecting the actual application effect.

Method used

By adding polyepoxysuccinic acid as a dispersant and γ-glycidyl etheroxypropyltrimethoxysilane/XH-CS05/stearic acid as a composite surface treatment agent, the nano calcium carbonate is surface treated to increase the electrostatic repulsion on the surface of the particles, reduce the agglomeration between particles, and improve the activation degree and dispersion.

Benefits of technology

It significantly improves the activation and dispersion of nano calcium carbonate, reduces the agglomeration between particles, improves its dispersion performance in polymers, and improves the overall performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119570289A_ABST
    Figure CN119570289A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of nano calcium carbonate with high dispersity and high activation degree. In the initial stage of the aging process, polyepoxysuccinic acid is adopted as a dispersing agent, and in the modification process, gamma-glycidyl ether oxypropyl trimethoxy silane / XH-CS05 / stearic acid is used for composite modification, so that the surface performance is greatly optimized, the hydrophilic performance is reduced, the closest distance between calcium carbonate particles is effectively increased, and the service life of the calcium carbonate particles is prolonged. Meanwhile, gaps among the particles are filled, mutual agglomeration of the calcium carbonate particles is successfully prevented, and the dispersity among the particles is improved. According to the prepared nano calcium carbonate with high dispersity and high activation degree, the activation degree is as high as 100%, the oil absorption value is 28g / 100g, the specific surface area BET value is 37.3668 m / g, and the nano calcium carbonate has the characteristics of high activation degree, low oil absorption value and relatively high specific surface area. The nano calcium carbonate modified by the method has the advantages of high activation degree, good dispersibility, simple process, convenient operation, easily available raw materials and the like, is easy to realize industrial production, and can be better applied to downstream products.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of calcium carbonate preparation, and particularly relates to a method for preparing nano calcium carbonate with high dispersibility and high activation degree. Background Art

[0002] As a high-quality inorganic filler, calcium carbonate is widely used in many industries such as rubber, plastics, cosmetics, coatings, inks, and medicine. With the ultra-fineness of calcium carbonate, the complexity of its structure and morphology, and the development of surface modification technology, as the particle size of calcium carbonate decreases, the surface electronic structure and crystal structure change, making it present a small size effect, surface effect, macro quantum tunneling effect, and quantum size effect, showing superior performance, further improving its application value; As the particle size of nano calcium carbonate decreases, it has a higher surface energy, the chemical activity of the particles is extremely large, the surface is highly polar, and it is easy to form agglomerates during the preparation and application process. In addition, the surface of calcium carbonate powder that has not been surface treated has hydrophilic and oleophobic properties, which makes it difficult to disperse evenly in polymers (plastics and other polymer materials), and its affinity with polymers is not good, which can easily cause interface defects and lead to a decrease in material performance. Moreover, as the amount of nano calcium carbonate filling increases, these shortcomings become more obvious, which seriously affects the actual application effect of nano calcium carbonate. Summary of the invention

[0003] In order to solve the above problems, the present invention provides a method for preparing nano calcium carbonate with high dispersibility and high activation. The method can increase the electrostatic repulsion on the surface of the particles, greatly reduce the agglomeration between the particles, reduce the surface energy of the particles, improve the activation of the nano calcium carbonate, and promote its dispersibility in the polymer.

[0004] The present invention adopts the following technical solution: A method for preparing nano calcium carbonate with high dispersibility and high activation degree comprises the following steps: (1) After the carbonization treatment, the aging process is performed, the nano-calcium carbonate slurry is transferred to an aging reaction tank, 0.5-1.5% of a dispersant based on the dry basis of nano-calcium carbonate is added to the nano-calcium carbonate slurry, and the mixture is stirred evenly to obtain a slurry of nano-calcium carbonate after the first treatment.

[0005] (2) The temperature of the nano-calcium carbonate slurry obtained in step (1) is raised to 75-80° C., aged for 2-3 hours, and then carbonized by carbon dioxide until the pH value drops below 7.5 to obtain nano-calcium carbonate slurry.

[0006] (3) adding the nano-calcium carbonate slurry obtained in step (2) into a surface treatment reaction tank, adjusting the stirring rate, and heating the temperature to between 80 and 85° C. to obtain a uniformly distributed nano-calcium carbonate suspension slurry; (4) Add 2.0-5.0% of the composite surface treatment agent based on the dry basis of nano-calcium carbonate to the nano-calcium carbonate suspension obtained in step (3), and continue stirring for 20-30 minutes to obtain the nano-calcium carbonate slurry after the second treatment; (5) The resulting nano-calcium carbonate slurry is filtered and dehydrated, dried at 100-130° C., crushed, and sieved to obtain nano-calcium carbonate powder with high dispersibility and high activation.

[0007] Wherein, the dispersant is polyepoxysuccinic acid, and the composite surface treatment agent is composed of a modifier (XH-CS05 Nanjing Xiehe Chemical), γ-glycidyloxypropyltrimethoxysilane and stearic acid; As a preferred technical solution of the present invention, the preparation method of the composite surface treatment agent is as follows: distilled water is heated to 90-100°C, then sodium hydroxide is added to the water, and stirred for 5-10 minutes to fully dissolve the sodium hydroxide. Stearic acid is then added for saponification reaction, and heating and stirring are continued for 40-60 minutes to obtain a saponified solution of stearic acid. γ-glycidyloxypropyltrimethoxysilane and XH-CS05 are then added in sequence, and stirring is continued with a glass rod until the stearic acid saponified solution is completely fused with γ-glycidyloxypropyltrimethoxysilane and XH-CS05.

[0008] As a preferred technical solution of the present invention, the amount of sodium hydroxide added is 10-15% of the amount of stearic acid added; the mass ratio of γ-glycidyloxypropyltrimethoxysilane / XH-CS05 / stearic acid composite surface treatment agent is 1-2:1-3:1-3; further preferably 1:2:2, 1:1:3, 1:3:1 and 2:1:2.

[0009] The beneficial effects of the present invention are: The present invention adds polyepoxysuccinic acid as a dispersant, and the dispersant is adsorbed on the surface of nano calcium carbonate, so that the nano calcium carbonate is charged with positive or negative charge by electrostatic physical adsorption, characteristic adsorption and the like, so that the surface of the nano calcium carbonate produces a double electric layer structure with a certain potential. With the addition of the polyepoxysuccinic acid dispersant, the electrostatic repulsion on the surface of the nano calcium carbonate is increased, so that the particles are difficult to further approach and agglomerate during thermal motion and Brownian motion. The surface modification adopts a composite modification method, which combines the advantages of multiple modifiers and improves the modification effect; the composite modification is carried out by γ-glycidyl ether oxypropyl trimethoxy silane, XH-CS05 and stearic acid. The surface properties of the nano calcium carbonate can be effectively changed, the distance between the particles is increased, the interaction of van der Waals forces is reduced, the mutual agglomeration between the nano calcium carbonate particles is prevented, and the surface activity of the nano calcium carbonate and the dispersibility between the particles are improved; the method of the present invention is simple in process and easy to operate, and the application performance of the nano calcium carbonate is greatly improved without changing the original production process. BRIEF DESCRIPTION OF THE DRAWINGS

[0010] Figure 1 This is the TEM image of Example 5.

[0011] Figure 2 This is the TEM image of Comparative Example 1.

[0012] Figure 3 This is the TEM image of Comparative Example 2. DETAILED DESCRIPTION

[0013] The technical scheme of the present invention will be described in detail below in conjunction with the embodiments and comparative examples, and the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.

[0014] Example 1 A method for preparing nano calcium carbonate with high dispersibility and high activation degree comprises the following steps: (1) After the carbonization treatment, the aging process is performed, the nano-calcium carbonate slurry is transferred to an aging reaction tank, 0.5% of a dispersant based on the dry basis of nano-calcium carbonate is added to the nano-calcium carbonate slurry, and the mixture is stirred evenly to obtain a slurry of nano-calcium carbonate after the first treatment.

[0015] (2) The temperature of the nano-calcium carbonate slurry obtained in step (1) was raised to 75° C. and aged for 3 h. After the aging, carbon dioxide was passed through for 30 min to carbonize until the pH value dropped to 7.0, thereby obtaining a nano-calcium carbonate slurry.

[0016] (3) Add the carbonized nano-calcium carbonate slurry into the surface treatment reaction tank, adjust the stirring rate, and heat the temperature to 85°C to obtain a uniformly distributed nano-calcium carbonate suspension slurry; (4) Add 5.0% of the composite surface treatment agent based on the dry basis of nano-calcium carbonate to the nano-calcium carbonate suspension obtained in step (3), and continue stirring for 30 minutes to obtain the nano-calcium carbonate slurry after the second treatment; (5) The final nano calcium carbonate slurry was filtered and dehydrated, dried at 110°C, crushed, and sieved to obtain the final product of nano calcium carbonate with an activation degree of 96.2%, an oil absorption value (DOP) of about 34g / 100gCaCO3, and a BET of 33.9812m 2 / g.

[0017] Wherein, the dispersant is polyepoxysuccinic acid, and the composite surface treatment agent is γ-glycidyloxypropyltrimethoxysilane / XH-CS05 / stearic acid composite surface treatment agent, and the mass ratio is 1:2:2; The preparation method of the composite surface treatment agent is as follows: distilled water is heated to 90° C., sodium oxide of 10% of the amount of stearic acid added is added to the distilled water, and the mixture is stirred for 10 minutes to fully dissolve the sodium hydroxide, and then stearic acid is added for saponification reaction, and heating and stirring are continued for 60 minutes to obtain a saponified solution of stearic acid, and then γ-glycidyloxypropyltrimethoxysilane and XH-CS05 are added in sequence, and stirring is continued with a glass rod until the stearic acid saponified solution is completely fused with the γ-glycidyloxypropyltrimethoxysilane and XH-CS05.

[0018] Example 2 A method for preparing nano calcium carbonate with high dispersibility and high activation degree comprises the following steps: (1) After the carbonization treatment, the aging process is performed, the nano-calcium carbonate slurry is transferred to an aging reaction tank, 0.5% of a dispersant based on the dry basis of nano-calcium carbonate is added to the nano-calcium carbonate slurry, and the mixture is stirred evenly to obtain a slurry of nano-calcium carbonate after the first treatment.

[0019] (2) The temperature of the nano-calcium carbonate slurry obtained in step (1) was raised to 75° C. and aged for 3 h. After the aging, carbon dioxide was passed through for 30 min to carbonize until the pH value dropped below 7.5 to obtain a nano-calcium carbonate slurry.

[0020] (3) Add the carbonized nano-calcium carbonate slurry into the surface treatment reaction tank, adjust the stirring rate, and heat the temperature to 85°C to obtain a uniformly distributed nano-calcium carbonate suspension slurry; (4) Add 5.0% of the composite surface treatment agent based on the dry basis of nano-calcium carbonate to the nano-calcium carbonate suspension obtained in step (3), and continue stirring for 30 minutes to obtain the nano-calcium carbonate slurry after the second treatment; (5) The final nano calcium carbonate slurry was filtered and dehydrated, dried at 110°C, crushed, and sieved to obtain the final product of nano calcium carbonate with an activation degree of 97.7%, an oil absorption value (DOP) of about 32g / 100gCaCO3, and a BET of 35.9651m 2 / g.

[0021] Wherein, the dispersant is polyepoxysuccinic acid, and the composite surface treatment agent is γ-glycidyloxypropyltrimethoxysilane / XH-CS05 / stearic acid composite surface treatment agent, and the mass ratio is 1:1:3; The preparation method of the composite surface treatment agent is as follows: distilled water is heated to 90° C., sodium oxide of 10% of the amount of stearic acid added is added to the distilled water, and the mixture is stirred for 10 minutes to fully dissolve the sodium hydroxide, and then stearic acid is added for saponification reaction, and heating and stirring are continued for 60 minutes to obtain a saponified solution of stearic acid, and then γ-glycidyloxypropyltrimethoxysilane and XH-CS05 are added in sequence, and stirring is continued with a glass rod until the stearic acid saponified solution is completely fused with the γ-glycidyloxypropyltrimethoxysilane and XH-CS05.

[0022] Example 3 A method for preparing nano calcium carbonate with high dispersibility and high activation degree comprises the following steps: (1) After the carbonization treatment, the aging process is performed, the nano-calcium carbonate slurry is transferred to an aging reaction tank, 0.5% of a dispersant based on the dry basis of nano-calcium carbonate is added to the nano-calcium carbonate slurry, and the mixture is stirred evenly to obtain a slurry of nano-calcium carbonate after the first treatment.

[0023] (2) The temperature of the nano-calcium carbonate slurry obtained in step (1) was raised to 75° C. and aged for 3 h. After the aging, carbon dioxide was passed through for 30 min to carbonize until the pH value dropped below 7.5 to obtain a nano-calcium carbonate slurry.

[0024] (3) Add the carbonized nano-calcium carbonate slurry into the surface treatment reaction tank, adjust the stirring rate, and heat the temperature to 85°C to obtain a uniformly distributed nano-calcium carbonate suspension slurry; (4) Add 5.0% of the composite surface treatment agent based on the dry basis of nano-calcium carbonate to the nano-calcium carbonate suspension obtained in step (3), and continue stirring for 30 minutes to obtain the nano-calcium carbonate slurry after the second treatment; (5) The final nano calcium carbonate slurry was filtered and dehydrated, dried at 110°C, crushed, and sieved to obtain the final product of nano calcium carbonate with an activation degree of 98.6%, an oil absorption value (DOP) of about 39g / 100gCaCO3, and a BET of 36.6024m 2 / g.

[0025] Wherein, the dispersant is polyepoxysuccinic acid, and the composite surface treatment agent is γ-glycidyloxypropyltrimethoxysilane / XH-CS05 / stearic acid composite surface treatment agent, and the mass ratio is 1:3:1; The preparation method of the composite surface treatment agent is as follows: distilled water is heated to 90° C., sodium oxide of 10% of the amount of stearic acid added is added to the distilled water, and the mixture is stirred for 10 minutes to fully dissolve the sodium hydroxide, and then stearic acid is added for saponification reaction, and heating and stirring are continued for 60 minutes to obtain a saponified solution of stearic acid, and then γ-glycidyloxypropyltrimethoxysilane and XH-CS05 are added in sequence, and stirring is continued with a glass rod until the stearic acid saponified solution is completely fused with the γ-glycidyloxypropyltrimethoxysilane and XH-CS05.

[0026] Example 4 A method for preparing nano calcium carbonate with high dispersibility and high activation degree comprises the following steps: (1) After the carbonization treatment, the aging process is performed, the nano-calcium carbonate slurry is transferred to an aging reaction tank, 0.5% of a dispersant based on the dry basis of nano-calcium carbonate is added to the nano-calcium carbonate slurry, and the mixture is stirred evenly to obtain a slurry of nano-calcium carbonate after the first treatment.

[0027] (2) The temperature of the nano-calcium carbonate slurry obtained in step (1) was raised to 75° C. and aged for 3 h. After the aging, carbon dioxide was passed through for 30 min to carbonize until the pH value dropped below 7.5 to obtain a nano-calcium carbonate slurry.

[0028] (3) Add the carbonized nano-calcium carbonate slurry into the surface treatment reaction tank, adjust the stirring rate, and heat the temperature to 85°C to obtain a uniformly distributed nano-calcium carbonate suspension slurry; (4) Add 5.0% of the composite surface treatment agent based on the dry basis of nano-calcium carbonate to the nano-calcium carbonate suspension obtained in step (3), and continue stirring for 30 minutes to obtain the nano-calcium carbonate slurry after the second treatment; (5) The final nano calcium carbonate slurry was filtered and dehydrated, dried at 110°C, crushed, and sieved to obtain the final product of nano calcium carbonate with an activation degree of 99.6%, an oil absorption value (DOP) of about 32g / 100gCaCO3, and a BET of 37.2351m 2 / g.

[0029] Wherein, the dispersant is polyepoxysuccinic acid, and the composite surface treatment agent is γ-glycidyloxypropyltrimethoxysilane / XH-CS05 / stearic acid composite surface treatment agent, and the mass ratio is 2:1:2; The preparation method of the composite surface treatment agent is as follows: distilled water is heated to 90° C., sodium oxide of 10% of the amount of stearic acid added is added to the distilled water, and the mixture is stirred for 10 minutes to fully dissolve the sodium hydroxide, and then stearic acid is added for saponification reaction, and heating and stirring are continued for 60 minutes to obtain a saponified solution of stearic acid, and then γ-glycidyloxypropyltrimethoxysilane and XH-CS05 are added in sequence, and stirring is continued with a glass rod until the stearic acid saponified solution is completely fused with the γ-glycidyloxypropyltrimethoxysilane and XH-CS05.

[0030] Example 5 A method for preparing nano calcium carbonate with high dispersibility and high activation degree comprises the following steps: (1) After the carbonization treatment, the aging process is performed, the nano-calcium carbonate slurry is transferred to an aging reaction tank, 1% of a dispersant based on the dry basis of nano-calcium carbonate is added to the nano-calcium carbonate slurry, and the mixture is stirred evenly to obtain a slurry of nano-calcium carbonate after the first treatment.

[0031] (2) The temperature of the nano-calcium carbonate slurry obtained in step (1) was raised to 75° C. and aged for 3 h. After the aging, carbon dioxide was passed through for 30 min to carbonize until the pH value dropped below 7.5 to obtain a nano-calcium carbonate slurry.

[0032] (3) Add the carbonized nano-calcium carbonate slurry into the surface treatment reaction tank, adjust the stirring rate, and heat the temperature to 85°C to obtain a uniformly distributed nano-calcium carbonate suspension slurry; (4) Add 5.0% of the composite surface treatment agent based on the dry basis of nano-calcium carbonate to the nano-calcium carbonate suspension obtained in step (3), and continue stirring for 30 minutes to obtain the nano-calcium carbonate slurry after the second treatment; (5) The final nano calcium carbonate slurry was filtered and dehydrated, dried at 110°C, crushed, and sieved to obtain a final product of nano calcium carbonate with an activation degree of 100%, an oil absorption value (DOP) of about 28g / 100gCaCO3, and a BET of 37.3668m 2 / g.

[0033] Wherein, the dispersant is polyepoxysuccinic acid, and the composite surface treatment agent is γ-glycidyloxypropyltrimethoxysilane / XH-CS05 / stearic acid composite surface treatment agent, and the mass ratio is 1:2:2; The preparation method of the composite surface treatment agent is as follows: distilled water is heated to 90° C., sodium oxide of 10% of the amount of stearic acid added is added to the distilled water, and the mixture is stirred for 10 minutes to fully dissolve the sodium hydroxide, and then stearic acid is added for saponification reaction, and heating and stirring are continued for 60 minutes to obtain a saponified solution of stearic acid, and then γ-glycidyloxypropyltrimethoxysilane and XH-CS05 are added in sequence, and stirring is continued with a glass rod until the stearic acid saponified solution is completely fused with the γ-glycidyloxypropyltrimethoxysilane and XH-CS05.

[0034] Example 6 A method for preparing nano calcium carbonate with high dispersibility and high activation degree comprises the following steps: (1) After the carbonization treatment, the aging process is performed, the nano-calcium carbonate slurry is transferred to an aging reaction tank, 1.0% dispersant based on the dry basis of nano-calcium carbonate is added to the nano-calcium carbonate slurry, and the mixture is stirred evenly to obtain the slurry of nano-calcium carbonate after the first treatment.

[0035] (2) The temperature of the nano-calcium carbonate slurry obtained in step (1) was raised to 75° C. and aged for 3 h. After the aging, carbon dioxide was passed through for 30 min to carbonize until the pH value dropped below 7.5 to obtain a nano-calcium carbonate slurry.

[0036] (3) Add the carbonized nano-calcium carbonate slurry into the surface treatment reaction tank, adjust the stirring rate, and heat the temperature to 85°C to obtain a uniformly distributed nano-calcium carbonate suspension slurry; (4) Add 5.0% of the composite surface treatment agent based on the dry basis of nano-calcium carbonate to the nano-calcium carbonate suspension obtained in step (3), and continue stirring for 30 minutes to obtain the nano-calcium carbonate slurry after the second treatment; (5) The final nano calcium carbonate slurry was filtered and dehydrated, dried at 110°C, crushed, and sieved to obtain the final product of nano calcium carbonate with an activation degree of 99.0%, an oil absorption value (DOP) of about 36g / 100gCaCO3, and a BET of 36.8428m 2 / g.

[0037] Wherein, the dispersant is polyepoxysuccinic acid, and the composite surface treatment agent is γ-glycidyloxypropyltrimethoxysilane / XH-CS05 / stearic acid composite surface treatment agent, and the mass ratio is 1:1:3; The preparation method of the composite surface treatment agent is as follows: distilled water is heated to 90° C., sodium oxide of 10% of the amount of stearic acid added is added to the distilled water, and the mixture is stirred for 10 minutes to fully dissolve the sodium hydroxide, and then stearic acid is added for saponification reaction, and heating and stirring are continued for 60 minutes to obtain a saponified solution of stearic acid, and then γ-glycidyloxypropyltrimethoxysilane and XH-CS05 are added in sequence, and stirring is continued with a glass rod until the stearic acid saponified solution is completely fused with the γ-glycidyloxypropyltrimethoxysilane and XH-CS05.

[0038] Example 7 A method for preparing nano calcium carbonate with high dispersibility and high activation degree comprises the following steps: (1) After the carbonization treatment, the aging process is performed, the nano-calcium carbonate slurry is transferred to an aging reaction tank, 1.0% dispersant based on the dry basis of nano-calcium carbonate is added to the nano-calcium carbonate slurry, and the mixture is stirred evenly to obtain the slurry of nano-calcium carbonate after the first treatment.

[0039] (2) The temperature of the nano-calcium carbonate slurry obtained in step (1) was raised to 75° C. and aged for 3 h. After the aging, carbon dioxide was passed through for 30 min to carbonize until the pH value dropped below 7.5 to obtain a nano-calcium carbonate slurry.

[0040] (3) Add the carbonized nano-calcium carbonate slurry into the surface treatment reaction tank, adjust the stirring rate, and heat the temperature to 85°C to obtain a uniformly distributed nano-calcium carbonate suspension slurry; (4) Add 5.0% of the composite surface treatment agent based on the dry basis of nano-calcium carbonate to the nano-calcium carbonate suspension obtained in step (3), and continue stirring for 30 minutes to obtain the nano-calcium carbonate slurry after the second treatment; (5) The final nano calcium carbonate slurry was filtered and dehydrated, dried at 110°C, crushed, and sieved to obtain the final product of nano calcium carbonate with an activation degree of 99.8%, an oil absorption value (DOP) of about 31g / 100gCaCO3, and a BET of 37.1624m 2 / g.

[0041] Wherein, the dispersant is polyepoxysuccinic acid, and the composite surface treatment agent is γ-glycidyloxypropyltrimethoxysilane / XH-CS05 / stearic acid composite surface treatment agent, and the mass ratio is 1:3:1; The preparation method of the composite surface treatment agent is as follows: distilled water is heated to 90° C., sodium oxide of 10% of the amount of stearic acid added is added to the distilled water, and the mixture is stirred for 10 minutes to fully dissolve the sodium hydroxide, and then stearic acid is added for saponification reaction, and heating and stirring are continued for 60 minutes to obtain a saponified solution of stearic acid, and then γ-glycidyloxypropyltrimethoxysilane and XH-CS05 are added in sequence, and stirring is continued with a glass rod until the stearic acid saponified solution is completely fused with the γ-glycidyloxypropyltrimethoxysilane and XH-CS05.

[0042] Example 8 A method for preparing nano calcium carbonate with high dispersibility and high activation degree comprises the following steps: (1) After the carbonization treatment, the aging process is performed, the nano-calcium carbonate slurry is transferred to an aging reaction tank, 1.0% dispersant based on the dry basis of nano-calcium carbonate is added to the nano-calcium carbonate slurry, and the mixture is stirred evenly to obtain the slurry of nano-calcium carbonate after the first treatment.

[0043] (2) The temperature of the nano-calcium carbonate slurry obtained in step (1) was raised to 75° C. and aged for 3 h. After the aging, carbon dioxide was passed through for 30 min to carbonize until the pH value dropped below 7.5 to obtain a nano-calcium carbonate slurry.

[0044] (3) Add the carbonized nano-calcium carbonate slurry into the surface treatment reaction tank, adjust the stirring rate, and heat the temperature to 85°C to obtain a uniformly distributed nano-calcium carbonate suspension slurry; (4) Add 5.0% of the composite surface treatment agent based on the dry basis of nano-calcium carbonate to the nano-calcium carbonate suspension obtained in step (3), and continue stirring for 30 minutes to obtain the nano-calcium carbonate slurry after the second treatment; (5) The final nano calcium carbonate slurry was filtered and dehydrated, dried at 110°C, crushed, and sieved to obtain the final product of nano calcium carbonate with an activation degree of 99.7%, an oil absorption value (DOP) of about 30g / 100gCaCO3, and a BET of 37.2460m 2 / g. .

[0045] Wherein, the dispersant is polyepoxysuccinic acid, and the composite surface treatment agent is γ-glycidyloxypropyltrimethoxysilane / XH-CS05 / stearic acid composite surface treatment agent, and the mass ratio is 2:1:2; The preparation method of the composite surface treatment agent is as follows: distilled water is heated to 90° C., sodium oxide of 10% of the amount of stearic acid added is added to the distilled water, and the mixture is stirred for 10 minutes to fully dissolve the sodium hydroxide, and then stearic acid is added for saponification reaction, and heating and stirring are continued for 60 minutes to obtain a saponified solution of stearic acid, and then γ-glycidyloxypropyltrimethoxysilane and XH-CS05 are added in sequence, and stirring is continued with a glass rod until the stearic acid saponified solution is completely fused with the γ-glycidyloxypropyltrimethoxysilane and XH-CS05.

[0046] Comparative Example 1 A method for preparing nano calcium carbonate with high dispersibility and high activation degree comprises the following steps: The surface of nano calcium carbonate is treated by adding a composite modifier without adding a dispersant, and the preparation method thereof comprises the following steps: (1) Add the carbonized nano-calcium carbonate slurry into the surface treatment reaction tank, adjust the stirring rate, and heat the temperature to 85°C to obtain a uniformly distributed nano-calcium carbonate suspension slurry; (2) Add 5.0% of the composite surface treatment agent based on the dry basis of nano-calcium carbonate to the nano-calcium carbonate suspension obtained in step (1), and continue stirring for 30 minutes to obtain nano-calcium carbonate slurry; (3) The final nano calcium carbonate slurry was filtered and dehydrated, dried at 110°C, crushed, and sieved to obtain the final product of nano calcium carbonate with an activation degree of 93.8%, an oil absorption value (DOP) of about 45g / 100gCaCO3, and a BET of 32.9428m 2 / g. .

[0047] The composite surface treatment agent is γ-glycidyloxypropyltrimethoxysilane / XH-CS05 / stearic acid composite surface treatment agent with a mass ratio of 1:2:2; The preparation method of the composite surface treatment agent is as follows: distilled water is heated to 90° C., sodium oxide of 10% of the amount of stearic acid added is added to the distilled water, and the mixture is stirred for 10 minutes to fully dissolve the sodium hydroxide, and then stearic acid is added for saponification reaction, and heating and stirring are continued for 60 minutes to obtain a saponified solution of stearic acid, and then γ-glycidyloxypropyltrimethoxysilane and XH-CS05 are added in sequence, and stirring is continued with a glass rod until the stearic acid saponified solution is completely fused with the γ-glycidyloxypropyltrimethoxysilane and XH-CS05.

[0048] Comparative Example 2 A method for preparing nano calcium carbonate with high dispersibility and high activation degree comprises the following steps: The surface of nano calcium carbonate is treated by adding a polyepoxysuccinic acid dispersant and a single stearic acid saponified liquid. The preparation method comprises the following steps: (1) After the carbonization treatment, the aging process is performed, the nano-calcium carbonate slurry is transferred to an aging reaction tank, 1.0% dispersant based on the dry basis of nano-calcium carbonate is added to the nano-calcium carbonate slurry, and the mixture is stirred evenly to obtain the slurry of nano-calcium carbonate after the first treatment.

[0049] (2) The temperature of the nano-calcium carbonate slurry obtained in step (1) was raised to 75° C. and aged for 3 h. After the aging, carbon dioxide was passed through for 30 min to carbonize until the pH value dropped below 7.5 to obtain a nano-calcium carbonate slurry.

[0050] (3) Add the carbonized nano-calcium carbonate slurry into the surface treatment reaction tank, adjust the stirring rate, and heat the temperature to 85°C to obtain a uniformly distributed nano-calcium carbonate suspension slurry; (4) Add 5.0% of the surface treatment agent based on the dry basis of nano-calcium carbonate to the nano-calcium carbonate suspension obtained in step (3), and continue stirring for 30 minutes to obtain nano-calcium carbonate slurry; (5) The final nano calcium carbonate slurry was filtered and dehydrated, dried at 110°C, crushed, and sieved to obtain the final product of nano calcium carbonate with an activation degree of 92.6%, an oil absorption value (DOP) of about 47g / 100gCaCO3, and a BET of 31.4120m 2 / g.

[0051] Wherein, the dispersant is polyepoxysuccinic acid, and the surface treatment agent is stearic acid saponified liquid; The preparation method of the surface treatment agent is as follows: distilled water is heated to 90° C., sodium oxide of 10% of the amount of stearic acid added is added to the distilled water, and the mixture is stirred for 10 minutes to fully dissolve the sodium hydroxide, and then stearic acid is added to carry out a saponification reaction, and the heating and stirring are continued for 60 minutes to obtain a saponified solution of stearic acid.

[0052] The nano calcium carbonate obtained by the above examples 1-8 and comparative examples 1-2 were compared and analyzed, and the performance results obtained were as follows: Table 1: Performance test results Experiment number Degree of activation (%) Oil absorption value (g / 100g) <![CDATA[BET(m 2 / g)]]> Example 1 96.2 34 33.9812 Example 2 97.7 32 35.9651 Example 3 98.6 30 36.9024 Example 4 99.6 32 37.1351 Example 5 100 28 37.3668 Example 6 99.0 36 36.8428 Example 7 99.8 31 37.1624 Example 8 99.7 30 37.2460 Comparative Example 1 93.8 45 32.9428 Comparative Example 2 92.6 47 31.4120 In summary, a method for preparing nano calcium carbonate with high dispersibility and high activation is to use polyepoxysuccinic acid as a dispersant and γ-glycidyloxypropyltrimethoxysilane / XH-CS05 / stearic acid as a composite modifier to perform composite modification to obtain an activation degree of 100%, an oil absorption value (DOP) of 28g / 100g, and a BET of 37.3668m 2 / g of nano calcium carbonate, the invention has the advantages of simple process, convenient operation, easy availability of raw materials, high activation degree and good dispersibility of the nano calcium carbonate product obtained by the reaction, and is easy to industrialize.

[0053] The above embodiments are only preferred implementation schemes of the present invention. The protection scope of the present invention is not limited to the above embodiments. All implementation methods derived from the ideas of the present invention belong to the protection scope of the present invention. In addition, for those skilled in the art, other different forms of changes or modifications can be made on the basis of the above description. It is not necessary and impossible to list all implementation schemes here. Any modifications, improvements, replacements, etc. derived from this are within the protection scope of the present invention.

Claims

1. A method for preparing nano calcium carbonate with high dispersibility and high activation, characterized in that: The steps include: (1) adding a dispersant to the nano-calcium carbonate slurry, stirring evenly, heating and aging, introducing carbon dioxide to carbonize until the pH value drops below 7.5, heating the temperature to between 80 and 85° C., and stirring to obtain a uniformly distributed nano-calcium carbonate suspension slurry; (2) Adding the composite surface treatment agent to the nano-calcium carbonate suspension slurry and stirring to mix well; (3) The obtained nano-calcium carbonate slurry is filtered and dehydrated, dried at 100-130° C., crushed, and sieved to obtain nano-calcium carbonate powder with high dispersibility and high activation degree.

2. The method for preparing a nano calcium carbonate with high dispersibility and high activation according to claim 1, wherein: The dispersant is polyepoxysuccinic acid, and the added mass thereof is 0.5-1.5% of the dry basis of nano-calcium carbonate.

3. The method for preparing a nano calcium carbonate with high dispersibility and high activation according to claim 1, wherein: The composite surface treatment agent is composed of a modifier XH-CS05, γ-glycidyloxypropyltrimethoxysilane and stearic acid, and the added mass thereof is 2.0-5.0% of the dry basis of nano-calcium carbonate.

4. The method for preparing a nano calcium carbonate with high dispersibility and high activation according to claim 3, wherein: The preparation method of the composite surface treatment agent comprises the following steps: heating distilled water to 90-100°C, then adding sodium hydroxide into the water, stirring for 5-10 minutes to fully dissolve the sodium hydroxide; then adding stearic acid for saponification reaction, continuously heating and stirring for 40-60 minutes to obtain a saponified solution of stearic acid; then sequentially adding γ-glycidyloxypropyltrimethoxysilane and XH-CS05, and continuously stirring with a glass rod until the saponified solution is completely fused with the γ-glycidyloxypropyltrimethoxysilane and XH-CS05.